Revisiting The Concept And Characteristics Of Islamic Resurgence In The Muslim World: Western And Muslim Scholars Perspectives - Mashitah Sulaiman; Abd Hakim Mohad @ Mohamad Ramli; Mohd Nazir Ahmad; Ros Aiza Mohd Mokhtar (Muslim Youth Movement of Malaysia (ABIM), 2024)
VOL. 1, NO 1 (JUNE) 2021: (Pages :1-18)